ENDOCRINE MARKERS AND DECLINE IN REPRODUCTIVE POTENTIAL OF WOMEN - BUSHRA FIZA; RATI MATHUR; MAHEEP SINHA; PUSHPENDRA SARASWAT (International Journal of Pharma and Bio Sciences, 2014)
As the chronological age increases, there is a physiological decline in reproductive potential of women. Moreover, the chronological age of women may not reflect the biological age of her ovaries. Various endocrine markers have been used to assess the ovarian reserve. The changing pattern of the endocrine markers; follicle stimulating hormone (FSH), luteinizing hormone (LH), estradiol (E2) and anti-Mullerian hormone (AMH) with the increasing age was observed to find out which of these best correlates with advancing reproductive age. The present study reveals that ovarian aging in women of reproductive age may not always coincide with their chronological age and some of the hormones may serve as distinct markers of ovarian aging.